HUBUNGAN BONDING ATTACHMENT DENGAN KEJADIAN POSTPARTUM BLUES PADA IBU POST SECTIO CAESAREA PRIMIPARA - Purwaningsih, Heni; Florencia Herlina Listyorini (Jurnal Kesehatan Madani Medika (JKMM), 2019)
Background: The period after childbirth causes the mother need adjustments to face her activities and new roles as a mother, so there are times when the mother experiences feelings of sadness related to her baby, this condition is called postpartum blues or baby blues. The exact cause of postpartum blues is not yet known. Mothers with postpartum blues can love, and care for their babies, but sometimes they can react negatively and not respond at all. This inconsistency in behavior can interfere with the bonding process between mother and baby, which affects the attachment between mother and baby. The purpose of this study is to determine the correlation between bonding attachment and postpartum blues in post sectio caesarea primipara mother at the RSIA Gladiool Magelang. Methods: Descriptive correlational research method with cross-sectional approach. The population were all post sectio caesarea primipara mothers at RSIA Gladiool Magelang with total sampling technique with sample of 73 respondents. Research measuring instruments used checklist. The data analysis used Chi Square test. Results: There is correlation between bonding attachment and postpartum blues in post sectio caesarea primipara mother at RSIA Gladiool Magelang (p value 0,000 (α = 0.05). Conclusion: There is correlation between bonding attachment and postpartum blues in post sectio caesarea primipara mother at RSIA Gladiool Magelang. Suggestion: Nurses can increase of combining care or bonding attachments for mothers to prevent postpartum blues.